Institutional and Economic Determinants of Ecological Fiscal Transfers in Indonesia - Puput Anggraeni Saputri; Novi Dirgantari; Iwan Fakhruddin; Ani Kusbandiyah (E-Jurnal Akuntansi, 2025)
This research aims to identify the factors that determine the allocation of ecological fiscal transfer, including the size of local governments, biodiversity program diversity, and revenue sharing from natural resources. The sampling method employs purposive sampling and is analyzed using multiple regression analysis. The population of this research is the local government that plans and implements ecological fiscal transfers recorded in the DJPK of the Ministry of Finance in 2021-2023 with an analysis sample of 32 data that implement and plan ecological fiscal transfer. The findings of this study suggest that the size of local governments and revenue sharing from natural resources positively influence ecological fiscal transfer, while the diversity of biodiversity programs negatively impacts ecological fiscal transfer.